How socio-technical regimes affect low-carbon innovation: Global pressures inhibiting industrial heat pumps in the Netherlands. (July 2022) - Wesseling, Joeri; Kieft, Alco; Fuenfschilling, Lea; Hekkert, Marko
Abstract: This paper shows that the socio-technical barriers that sustainable innovations face, may stem from global regimes. Existing transitions approaches like the Technological Innovation System (TIS), overlook the impact of global regimes on radical innovation. Building on institutional theory, we therefore develop a theoretical framework that captures TIS-regime interaction, allowing us to analyze the impact of globalized industries on the development and diffusion of promising radical low-carbon innovations. This is applied to a qualitative case study of how the global industrial processing regime influenced the Dutch industrial heat pump (IHP) TIS over the past 30 years. We identify several mechanisms through which the regime's coercive, normative and mimetic institutional pressures inhibit TIS development. Takeovers by multinational owners for example translated into corporate strategies focused on short-term economic valuation with no priority to sustainability. TIS actors respond to and strategically deal with these pressures. We show that the institutionalization of a new logic in the global regime can outpace the rate of technological development of the radical innovation, causing it to become less attractive over time despite technological performance increases. The impact of global regimes limits the effectiveness of national policy support for a TIS.